2004
DOI: 10.1152/ajpcell.00541.2003
|View full text |Cite
|
Sign up to set email alerts
|

Palytoxin disrupts cardiac excitation-contraction coupling through interactions with P-type ion pumps

Abstract: Palytoxin is a coral toxin that seriously impairs heart function, but its effects on excitation-contraction (E-C) coupling have remained elusive. Therefore, we studied the effects of palytoxin on mechanisms involved in atrial E-C coupling. In field-stimulated cat atrial myocytes, palytoxin caused elevation of diastolic intracellular Ca 2ϩ concentration ([Ca 2ϩ ]i), a decrease in [Ca 2ϩ ]i transient amplitude, Ca 2ϩ alternans followed by [Ca 2ϩ ]i waves, and failures of Ca 2ϩ release. The decrease in [Ca 2ϩ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Palytoxin transforms the sodium pump into a nonselective cation channel and has been shown to increase firing in various tissues (Frelin and van Renterghem 1995;Kockskämper et al 2004;Sheridan et al 2005). This is also the case for SCN neurons as recorded with both cell-attached and whole cell modes (Fig.…”
Section: Palytoxin Effectsmentioning
confidence: 73%
“…Palytoxin transforms the sodium pump into a nonselective cation channel and has been shown to increase firing in various tissues (Frelin and van Renterghem 1995;Kockskämper et al 2004;Sheridan et al 2005). This is also the case for SCN neurons as recorded with both cell-attached and whole cell modes (Fig.…”
Section: Palytoxin Effectsmentioning
confidence: 73%
“…Indeed, Artigas and Gadsby demonstrated that Pltx and ouabain can simultaneously bind to Na + /K + -AtPase (Artigas and Gadsby, 2004), suggesting the possibility of two different binding sites on the pump, as also confirmed by Pelin and colleagues (Pelin et al, 2013a). Pltx toxins were also shown to affect other membrane ion transport components (Frelin and Van Renterghem, 1995;Ikeda et al, 1988;Muramatsu et al, 1984;Sauviat, 1989;Kockskamper et al, 2004): the toxin could also interfere with other P-type AtPases such as the sarcoplasmic endoplasmatic reticulum Ca 2+ pump (SeRCA) (Coca et al, 2008;Kockskamper et al, 2004) and the non-gastric Na + /K + AtPase pump (Qiu et al, 2006;Scheiner-Bobis et al, 2002).…”
Section: Mode Of Actionmentioning
confidence: 82%
“…Intracellular Na + accumulation induces the transport of Ca 2+ into the cells via Na + /Ca 2+ exchangers (Frelin and Van Renterghem, 1995;Ikeda et al, 1988;Kockskamper et al, 2004;Vale et al, 2006). the latter increased intracellular Ca 2+ concentration affects skeletal, heart and smooth muscle cells (Frelin and Van Renterghem, 1995;Ito et al, 1977;Karaki et al, 1988;Kockskamper et al, 2004;Nagase and Karaki, 1987;Vale et al, 2006).…”
Section: Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the molecular action of PlTX skeletal, heart and smooth muscle cells are the major targets of PlTX among excitable cells, responding with contraction induced both directly, following the increased intracellular Ca 2+ concentrations (Ito et al, 1977;Frelin and Van Renterghem, 1995;Kockskämper et al, 2004), and indirectly, through the Ca 2+ -induced release of neurotransmitters (Nagase and Karaki, 1987;Karaki et al, 1988). …”
Section: Mechanistic Considerationsmentioning
confidence: 99%